2004
DOI: 10.1038/sj.tpj.6500272
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor 2 and progesterone receptor gene polymorphisms and lipid levels in women with different hormonal status

Abstract: Sex steroid hormones have multiple effects on lipid metabolism. We investigated the association between two common single nucleotide polymorphisms of the estrogen receptor 2 gene (ESR2), 1082G4A and 1730A4G, and PROGINS polymorphism of the progesterone receptor gene (PGR) with lipoprotein levels in a cross-sectional study with 472 women of European descent. The women were classified into three subgroups according to hormonal status, premenopausal women (n ¼ 187; mean age ¼ 3479.7 years), postmenopausal women e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
1
25
2
1
Order By: Relevance
“…However, Almeida et al 29 did not observe a similar association in postmenopausal women on estrogen therapy after 4 months of treatment. Although we detected associations between ER-α XbaI polymorphisms and tamoxifen-induced lipid changes, we observed none with ER-α PvuII.Almeida et al 30 have recently reported an association between ER-β and the response of serum lipids in 472 women unexposed or exposed to estrogen therapy for at least 4 months. They found that LDL-cholesterol concentrations were associated with ER-β 1082 G-A (rs1256049) in pre-or postmenopausal women if they received estrogen.…”
contrasting
confidence: 38%
See 2 more Smart Citations
“…However, Almeida et al 29 did not observe a similar association in postmenopausal women on estrogen therapy after 4 months of treatment. Although we detected associations between ER-α XbaI polymorphisms and tamoxifen-induced lipid changes, we observed none with ER-α PvuII.Almeida et al 30 have recently reported an association between ER-β and the response of serum lipids in 472 women unexposed or exposed to estrogen therapy for at least 4 months. They found that LDL-cholesterol concentrations were associated with ER-β 1082 G-A (rs1256049) in pre-or postmenopausal women if they received estrogen.…”
contrasting
confidence: 38%
“…Almeida et al 30 have recently reported an association between ER-β and the response of serum lipids in 472 women unexposed or exposed to estrogen therapy for at least 4 months. They found that LDL-cholesterol concentrations were associated with ER-β 1082 G-A (rs1256049) in pre-or postmenopausal women if they received estrogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, mean LDL and total cholesterol concentrations in premenopausal or postmenopausal women with higher estrogen exposure were lower in those with the GA genotype for 1082A4G than in those with the AA genotype in Brazilians of European descent. 29 Conversely, Domingues-Montanari et al 46 reported that no association with MI was observed for 1082A4G or 1730A4G in the Spanish population. In this study, we did not find any association of 1082A4G (rs1256049) and 1730A4G (rs4986938) with hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 1082A4G (rs1256049) and 1730A4G (rs4986938) of ESR2 might have a role in CVDs 26,27 and lipid profile. 28,29 Most of the evidence was reported from the Western population; however, little was known about the SNP distributions of ESRs and their relationships with hyperlipidemia in Chinese women. In our study, we measured serum estrogen concentration and sequenced four representative SNPs, namely PvuII (rs2234693) and XbaI (rs9340799) of ESR1 and 1082A4G (rs1256049) and 1730A4G (rs4986938) of ESR2.…”
Section: Introductionmentioning
confidence: 99%